An analysis of movements with or without back bend of the trunk or large hip extension in 1st Juniors` Rhythmic Gymnastics World Championship-2019. Is there injury risk for gymnasts? - Agopyan, A. (International Journal of Performance Analysis in Sport, 2021)
The aim of this study is to determine and compare the rate of use of body movement difficulties and elements with or without back band of the trunk or large hip extension of gymnasts who participated in the 1st Junior`s Rhythmic Gymnastics World Championship-2019. A total of 244 routines of 136 individual rhythmic gymnasts were analysed. Analyses were made on rope, ball, clubs and ribbon apparatus, each consisting of 61 series. All body movement difficulties were determined according to their type (with or without back band of the trunk or large hip extension with trunk), overall repetition numbers and repetition numbers for each apparatus. The hyperextension group elements were also identified from the pre-acrobatic group or body waves. The hyperextension group elements, and total of number of elements and body difficulties together with hyperextension were significantly higher (with very large effect size:1.332-2.180; p < 0.05) than without hyper extensional body movement difficulties. It is thought that the use of hyperextension movements with such intensity may increase the risk of injury in collumna vertebralis and hip region in rhythmic gymnasts. Therefore, some changes about the movements requiring a high degree of flexibility should be made immediately in the completion rules.